From Here to Eternity: Two Absolutists (Newton, Clarke) and Two Relationalists (Leibniz, Kant of New Elucidation) on the Essence of Time with a Consideration of Their Similarities and Differences - Helenius, Visa (Turun yliopisto, 2025)
A dispute about absolute and relative time in the eighteenth-century is famous and much discussed. According to the absolutist view, endorsed by Isaac Newton and Samuel Clarke, time is an absolute entity, whose existence does not require other beings except God. In the relationalist view, which is endorsed by G. W. Leibniz and the pre-critical Immanuel Kant, the absolutist position is denied since time is, the relationalists believe, a relational entity, which emerges from relations of beings. In this article, I examine the dispute by reviewing the views of the above-mentioned four philosophers. My aims are, first, to shed light on the philosophy of time by examining the views, and second, to argue that, in addition to the fundamental difference between the absolutist and the relationalist view concerning the ontological status of time, there are other differences, and that they share some features.
True Colors, Time After Time: Essays Honoring Valtteri Arstila